2014
DOI: 10.1007/s10681-014-1078-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cold tolerance at early developmental stages and allelic variation at candidate genes in South American rice germplasm

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media Dordrecht. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The MYBS3 transcriptional network responds more slowly than the CBF pathway to low temperatures, regulating low-temperature tolerance genes such as those involved in the repression of the CBF pathway, which distinguishes it as an independent low-temperature responsive cascade 120 . In addition, several QTLs [121][122][123] have been identified that may be exploited to obtain low-temperature yield stability in rice.…”
Section: Solutions For Aluminium and Boron Toxicitymentioning
confidence: 99%
“…The MYBS3 transcriptional network responds more slowly than the CBF pathway to low temperatures, regulating low-temperature tolerance genes such as those involved in the repression of the CBF pathway, which distinguishes it as an independent low-temperature responsive cascade 120 . In addition, several QTLs [121][122][123] have been identified that may be exploited to obtain low-temperature yield stability in rice.…”
Section: Solutions For Aluminium and Boron Toxicitymentioning
confidence: 99%
“…identified a single nucleotide polymorphism (SNP) in OsGSTZ2 (c.295A [ G), which strongly correlated with CTS in 76 indica and japonica rice varieties. Moreover, Pachecoy et al (2014) reported the same SNP correlated with CTS in 116 rice inbred lines and varieties from South America. These researchers analyzed several genotypes such as the susceptible cultivars IR50, IRGA417, IRGA409 (spp.…”
Section: Discussionmentioning
confidence: 86%